Comparison of fixed and living biological cells parameters investigated with digital holographic microscope - Nienałtowski, Patryk; Baczewska, Maria; Kujawińska, Małgorzata (Photonics Letters of Poland, 2020)
The statistical analysis and comparison of biophysical parameters of living and fixed, mouse embryonic fibroblasts cells are presented. The parameters are calculated based on phase measurements performed by means of a digital, holographic microscope. The phases are retrieved from off-axis, image plane holograms, followed by custom image segmentation and statistical analysis of cells’ surface, phase volume and dry mass. The results indicated statistically significant differences between fixed and living cell parameters, which is an important message for setting methodology for further diagnosis based on quantitative phase (label-free) analysis. Full Text: PDF References: K. Alm, et al. "Cells and Holograms – Holograms and Digital Holographic Microscopy as a Tool to Study the Morphology of Living Cells", InTech, 2013. [CrossRef] Y. Rivenson, Y. Wu, A. Ozcan, Light: "Deep learning in holography and coherent imaging", Science & Applications, 8, Art. No. 85 (2019) [CrossRef] Min, et al. Optics Letters, 42, Issue 2, pp. 227-230, (2017) [CrossRef] M. Baczewska, Measurements and analysis of cells and histological skin sections based on digital holographic microscopy, WUT master thesis, 2018. [CrossRef] P. Stępień, D. Korbuszewski, M. Kujawińska, "Digital Holographic Microscopy with extended field of view using tool for generic image stitching", ETRI Journal, 41(1), 73-83, (2019). [CrossRef] S. Beucher, Serge, The Watershed Transformation Applied To Image Segmentation, Scanning microscopy. Supplement 6, (2000) [DirectLink] J. A. Hartigan, M. A. Wong, "A K-Means Clustering Algorithm", Applied Statistics, (1979) [CrossRef] J. Serra, Image Analysis and Mathematical Morphology, Academic Press, (1982) [DirectLink] P. Girshovitz, N. T. Shaked, "Generalized cell morphological parameters based on interferometric phase microscopy and their application to cell life cycle characterization", Biomedical Optics Express Vol. 3, Issue 8, pp. 1757-1773, (2012) [CrossRef]